Do the maths: An analysis of the gender gap in mathematics in Africa. (June 2015) - Dickerson, Andy; McIntosh, Steven; Valente, Christine
Highlight: We examine the maths gender gap in primary schools in 19 African countries. There is a significant difference in maths test scores in favour of boys overall. The gap cannot be explained by gender differences in observable characteristics. However, the gender gap varies widely with regional characteristics. This variation suggests that simple genetic explanations are insufficient. Abstract: This paper uses microdata for 19 African countries to examine the gender difference in maths test scores amongst primary school children. There is a significant difference in maths test scores in favour of boys, similar to that previously observed in developed countries. This difference cannot be explained by gender differences in school quality, home environment, or within-school gender discrimination in access to schooling inputs. However, the gender gap varies widely with characteristics of the regions in which the pupils live, and these regional characteristics are more predictive of the gender gap than parental education and school characteristics, including teacher gender. At the cross-country level, differences in fertility rates account for nearly half the variation in the gender gap, and this relationship is not due to the correlation between fertility and GDP.